The Urgency of Artificial Intelligence (AI) Technology Utilization in the Physical Security Sector: A Literature Review - Farid Alfarisi; Surya Nita; Chairul Muriman Setiabudi (Transpublika Publisher, 2025)
The increasing crime rate in Indonesia has led the public to question the effectiveness of the country's security systems, particularly physical security. This situation is further complicated by rapid technological advancements, which allow criminal acts to evolve in both motive and method. This article discusses the urgency of utilizing artificial intelligence (AI) technology in the physical security sector through a review of national and international literature. The literature analyzed in this study includes publications from the last ten years that are relevant to the topics of physical security and artificial intelligence. Key focus areas of this literature review include global trends in AI implementation in physical security, the benefits of its application, and the challenges faced during implementation. The findings reveal that the integration of AI, including the use of IoT devices, intelligent surveillance cameras, and biometric access control systems, can significantly improve the effectiveness of threat detection, prevention, and real-time response. However, in Indonesia, the application of AI in physical security remains limited due to infrastructure constraints, lack of human resource readiness, underdeveloped regulations, data privacy concerns, and high investment requirements. This study concludes that the application of AI in physical security is essential for enhancing safety, particularly in confined environments such as offices, residential areas, and commercial zones, in order to mitigate the rising trend of physical crimes.